Profile of Patients at Pediatric Emergency Services Soetomo Hospital Surabaya - Ira Dharmawati; Arina Setyaningtyas; Neurinda Permata Kusumastuti (Jurnal Ners, 2012)
Introduction: Installation service system at the Emergency Department (ED) Soetomo Hospital is a coordinated and integrated system under one roof. Include emergency medical and emergency surgery in a very important component of health services at each hospital. The information published on the patient proﬁle and the usefulness of emergency care services indeveloping countries and developed countries is still very rare. This study aimed to describe the characteristic of patients attending the ED at Soetomo hospital Surabaya.Method: This study was a retrospective study. The proﬁle of patients visiting the ED for 1 year were recorded and presented descriptively.Result: The total number of patients visiting the hospital was 5,835, with a monthly average of 486 patients. The children at the age of 1–5 years presented the largest age group (33.6%). The main diagnosis was respiratory tract infection (31%), diarrhea (17.%), followed by seizure (12.4%). The overall mortality rate was 1.7%.Discussion: Respiratory tract infection in children at the age of 1–5 years still count as a major problem at Soetomo Hospital Surabaya.